Intermittent Fasting Modulation of the Diabetic Syndrome in Streptozotocin- Injected Rats: Post-Mortem Investigations - Belkacemi, Louiza; Selselet-Attou, Ghalem; Antoine, Marie-Hélène; Nortier, Joelle; Hupkens, Emeline; Sener, Abdullah; Malaisse, Willy J. (The Open Physiology Journal, 2013)
Intermittent fasting was previously reported to exert beneficial effects in sand rats, an animal model of diabetes. The present report complements recent comparable findings recorded in streptozotocin-induced diabetic rats (STZ rats). Intermittent fasting minimized the increase in pancreatic, hepatic and renal weight otherwise observed in the STZ rats. The glycogen content of the liver was higher in the STZ rats than in the control animals. It was positively correlated, at the individual level, with the hepatic glucose content. Significant positive correlations also prevailed between the plasma glucose concentration at sacrifice, which was lower in intermittently fasting or calorie-restricted STZ rats than in nonfasting STZ rats, and either the liver glucose content or liver total carbohydrate content. The kidney PCNA (proliferating cell nuclear antigen) index, as well as the plasma creatinine and urea concentrations, were also lower in intermittently fasting or calorie-restricted STZ rats than in non-fasting diabetic animals. These findings reinforce the view that intermittent fasting may exert a favourable effect, in terms of glucose homeostasis and the undesirable consequences of its perturbation,in diabetic animals.
Keywords: Streptozotocin-induced diabetic rats, kidney proliferating cell nuclear antigen, liver histology, intermittent fasting, caloric restriction.